WEIGHT MANAGEMENT PROGRAM FOR PATIENTS WITH DIABETES MELLITUS TYPE 2 TREATED WITH ORLISTAT – OUR EXPERIENCES - Jelka Zaletel; Andrej Janež; Andreja Kocijančič (Zdravniški Vestnik, 2003)
Background. Obesity is an important risk factor in cardiovascular morbidity and mortality. Type 2 diabetic patients loose less weight than non-diabetics. Type 2 diabetic patients loose less weight than non-diabetics and thus a program for weight management in type 2 diabetic patients was established. Patients were treated with orlistat. Methods. 31 patients were included having body mass index (BMI) above 27 kg/m2 not treated with acarbose or insulin. Four patients dropped out. In the first month individual counselling and education were offered. The goals of the program were weight loss and an improvement of glucose, lipid and blood pressure control. Six-month therapy with orlistat followed accompained with weekly group meetings. Results. Clinically and statistically significant decreases that were relevated are as follows: body weight by 10.9 (standard deviation 6.8, p = 0.009) kg, fasting blood glucose by 2.1 (2.1, p = 0.0003) mmol/l, HbA1c by 1.4 (1.2, p = 0.0001)%, triglycerides by 0.52 (1.1, p = 0.049) mmol/l, systolic blood pressure by 12.1 (20.5, p = 0.028) mmHg, in patients with dyslipidemia total cholesterol by 0.4 (0.7, p = 0.032) mmol/l. Conclusions. Treatment with orlistat, added upon intensive education program, can significantly decrease body weight and improve the whole profile of cardiovascular risk factors. During the program, patients gradually adapted their diet and behaviour. Therefore, this program could provide a solid ground for lifelong lifestyle changes of obese type 2 diabetic patients.